A Matrix-Assisted Laser Desorption/Ionization—Mass Spectrometry Assay for the Relative Quantitation of Antennary Fucosylated N-Glycans in Human Plasma - Rebello, Osmond D.; Nicolardi, Simone; Lageveen-Kammeijer, Guinevere S. M.; Nouta, Jan; Gardner, Richard A.; Mesker, Wilma E.; Tollenaar, Rob A. E. M.; Spencer, Daniel I. R.; Wuhrer, Manfred; Falck, David (Frontiers in Chemistry, 2020)
Changes in the abundance of antennary fucosylated glycans in human total plasma N-glycome (TPNG) have been associated with several diseases ranging from diabetes to various forms of cancer. However, it is challenging to address this important part of the human glycome with high-throughput techniques. Most commonly, time-consuming chromatographic separations are performed to differentially quantify core and antenna fucosylation. We introduce a high-throughput matrix-assisted laser desorption/ionization – mass spectrometry (MALDI-MS) assay for the relative quantitation of antennary fucosylation in TPNG. N-linked glycans are released from plasma by PNGase F and further treated with a core fucosidase before performing a linkage-informative sialic acid derivatization. The core fucosylated glycans are thus depleted while the remaining antennary fucosylated glycans are quantitated. Simultaneous quantitation of α2,3-linked sialic acids and antennary fucosylation allows an estimation of the sialyl-Lewis x motif. The approach is feasible using either ultrahigh-resolution Fourier-transform ion cyclotron resonance mass spectrometry (MALDI-FT-ICR-MS) or time-of-flight mass spectrometry (MALDI-TOF-MS). The assay was used to investigate changes of antennary fucosylation as clinically relevant marker in 14 colorectal cancer (CRC) patients. In accordance with a previous report, we found elevated levels of antennary fucosylation pre-surgery which decreased after tumor resection. The assay has the potential for revealing antennary fucosylation signatures in various conditions including diabetes and different types of cancer.